2004
DOI: 10.1115/1.1924486
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Tuned Bladed Disk Response to Frequency Veering

Abstract: A continuous method is presented for representing the mode interaction that occurs in frequency veering in terms of the nominal sector modes of a cyclic symmetric bladed disk model constrained at a reference interblade phase angle. Using this method, the effect of frequency veering on the mode shapes can be considered in the context of the generalized forces exciting the system and the modal response of the bladed disk. It is shown that in a blade-dominated family of modes, the transfer of modal energy to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It can be shown that the eigenmodes corresponding to localized blade modes are characterized by straight lines contrary to the eigenmodes corresponding to global coupled disk-blade modes. It is well known that the mistuning important effects of response amplification are concentrated in "veering" zones for which the coupling between the disk motion and the blade motion is high [1,[27][28][29]. Indeed, in such veering zones, the tuned responses are known to be inhibited with respect to the ones corresponding to pure blade mode excitations, due to the repartition of the mechanical energy between disk and blade modes.…”
Section: Strategy For the Construction Of The External Loadmentioning
confidence: 96%
“…It can be shown that the eigenmodes corresponding to localized blade modes are characterized by straight lines contrary to the eigenmodes corresponding to global coupled disk-blade modes. It is well known that the mistuning important effects of response amplification are concentrated in "veering" zones for which the coupling between the disk motion and the blade motion is high [1,[27][28][29]. Indeed, in such veering zones, the tuned responses are known to be inhibited with respect to the ones corresponding to pure blade mode excitations, due to the repartition of the mechanical energy between disk and blade modes.…”
Section: Strategy For the Construction Of The External Loadmentioning
confidence: 96%
“…It can be seen that the first frequency veering region locates between the first and second modal family, and the second locates between the third and fourth modal family as shown in Figure 2. Mode shapes which locate in the frequency veering regions are mixed blade disk motion [16][17][18].…”
Section: Sensitivity Of Degree Of Double Natural Frequencies Split Ofmentioning
confidence: 99%
“…At these specific angular velocities the natural frequencies of the system and the mode shapes will converge, interact and then veer apart without crossing. Such phenomenon, known as frequency veering [15], can be detected among the basis modes and the parametric mode components of order ±1 and −2. Due to this frequency veering, the natural frequency of the basis mode component denoted by M5 will not, in fact, correspond to the fifth mode at all velocities.…”
Section: Measures Of Modal Controllability and Observabilitymentioning
confidence: 99%
“…This paper is though devoted to vertical bladed rotors in which the periodic excitation due to gravity and blade weights does not play a significant role. From the theoretical viewpoint the main contributions are: i) the modal controllability and observability and their dependency on stiffening and frequency veering effects [15] are carefully quantified in the absence of periodic excitation induced by the gravity; ii) it is shown how and why the introduction of deliberate blade mistuning makes the bladed rotor controllable and observable using only shaft-based actuation and sensing; iii) the influence of the rotational speed on the degrees of controllability and observability is investigated; iv) the influence of mistuning patterns on the controllability of vertical bladed rotors with different number of blades is also examined. Finally, the test rig was modified in order to test vertical bladed rotors.…”
Section: Introductionmentioning
confidence: 99%